Magma Plumbing System at Izu-Oshima Volcano, Japan: Constraints From Petrological and Geochemical Analyses - Kuritani, Takeshi; Yamaguchi, Azusa; Fukumitsu, Sayuki; Nakagawa, Mitsuhiro; Matsumoto, Akiko; Yokoyama, Tetsuya (Frontiers in Earth Science, 2018)
The Izu-Oshima volcano is one of the most active volcanoes in Japan, and has generated relatively large-scale eruptions every 30–40 years for the past 200 years. As more than 30 years have passed since the last eruptions in 1986–87, volcanic activity is expected to resume in the near future. To help elucidate the current and future state of the volcano’s magma system, the temporal evolution of the recent magma plumbing system was investigated through a petrological and geochemical analysis of its basaltic lavas and pyroclastics (<~53 wt.% of SiO2) that were erupted during the last ~1.5 kyrs. The basaltic products have variable phenocryst contents, ranging from ~0 to ~20 vol.%, and phenocryst-bearing samples commonly contain plagioclase, orthopyroxene, and clinopyroxene phenocrysts. The whole-rock compositions are significantly scattered in the Harker variation diagrams, suggesting that the compositional diversity was established by at least two independent magmatic processes. The application of principal component analysis on the whole-rock major element data suggests that one magmatic process was crystal fractionation of crystal-poor magmas, and the other process was either plagioclase accumulation or mixing of plagioclase-rich magmas. Based on this observation, and combined with the petrological analysis and previous geophysical studies, we propose that aphyric magmas, stored in an 8–10 km-deep magma chamber, progressively differentiated over time from the 7th to 20th century. Furthermore, the compositional variations in basalts resulted from the mixing of the differentiating aphyric magmas with variable proportions of porphyritic magmas derived from a 13–18 km-deep magma chamber. Because recent eruptions have been triggered by the ascent of porphyritic magma from the 13–18 km-deep magma chamber, and its injection into the 8–10 km-deep magma chamber, it is important to monitor the deeper magma chamber to predict future volcanic activity.